Cross-sectional ARDL analysis to access the impact of stressful living environment and extreme weather events on youth's education - Pedro Neves Mata; Shahzad Ali; Jo\~ao Luis Lucas; Jéssica Nunes Martins; Mahwish Zafar (Economies, 2023)
This study's primary objective is to investigate the impact of stressful living environments and extreme weather conditions on youth's education. For the fulfillment of this objective, the unique and latest methodology, such as second-generation unit root, cross-sectional ARDL, and the Westerlund approach are used on panel data taken from India and Pakistan. The cross-sectional dependency test is also employed to determine the internal correlations between cross-sections. The results indicate that there are long- as well as short-run relationships between variables. This study helps to develop policies to manage natural disasters, as well as provide the theoretical background to reduce the stressful living environment.
Keywords: 330; stressful living environment; extreme weather events; education; cross-sectional dependency; CS-ARDL